Pemanfaatan minyak jelantah menjadi sabun batang pada masyarakat kelurahan Air Hitam Pekanbaru - Annie Mustika Putri; Yaumul Fazri; Tauhid Abdul Ghani Setyo Wibowo; Dini Maharani Putri (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Every cooking activity in households inevitably generates waste commonly known as waste or garbage, whether in solid or liquid form. One of these wastes is used cooking oil, commonly referred to as used cooking oil or "Minyak Jelantah". Environmental awareness plays a crucial role in promoting community consciousness toward the surrounding environment. Unfortunately, improper waste disposal, including used cooking oil, is a common practice among the public, leading to environmental pollution and adverse effects on human health. Used cooking oil results from repeated use in cooking, causing an increase in acid and peroxide levels and containing carcinogenic compounds. This community outreach program aims to educate and train the residents of Air Hitam Village, Pekanbaru, on the proper utilization of used cooking oil by transforming it into solid soap. The implementation of the program involves preparatory measures, practical soap-making sessions, and ongoing mentoring and support. The program's outcomes reveal an increased understanding among the community regarding the beneficial utilization of used cooking oil and a heightened awareness of the importance of preserving both the environment and personal health. Moreover, the production of solid soap from used cooking oil is expected to create an additional source of income for the local community and the Waste Bank group. This outreach initiative has successfully fostered a greater sense of environmental and health consciousness among the residents of Air Hitam Village